Kinerja Karyawan ditinjau dari Budaya Organisasi, Kepuasan Kerja dan Religiusitas - Qomariah Lahamid; Novia Hairunnisa; Ilham Chanra Putra (Pelantar Press, 2022)
This study aims to determine the effect of organizational culture, job satisfaction and religiosity on the performance of PTPN V employees, Sei Galuh District, Kampar Regency using primary data obtained by distributing questionnaires to 32 respondents. The data analysis method used is multiple linear regression. The results showed that the variables of organizational culture, job satisfaction and religiosity had an effect on employee performance either partially or simultaneously. Based on the results of the multiple linear regression test, organizational culture has greater results than other variables, which is 0.853. The value of R Square is 0.971, this shows that the variables of organizational culture, job satisfaction and religiosity, as a whole have an effect of 97.1% on performance while the remaining 2.9% is influenced by other variables not examined in this study.